ANALISIS PENGARUH KOMPETENSI PROFESIONAL, KREDIBILITAS, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PILOT - Tuty Sri Liestiati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
The purpose of this study is to determine how much influence professional competence, credibility and emotional intelligent toward pilot performance, either partially or simultaneously. The research design used in the preparation of this research is quantitative, aimed to determine the effect of independent variables on the dependent. The study applied descriptive and deductive of multivariate regression method it’s include 91 respondents as the samples. The samples were selected through simple random sampling. The statistical tool were used is SPSS Software as the means to examine the data. Hypothesis testing based on determinate coefficient (R2) of 76,2% can be summed up the effect of the variable independent to variable Y where the influence are positive either partially or simultaneously. The results of this research can be stated that the multiple correlation is significant. Thus the null hypothesis (H0) that states there are no effect between professional competence, credibility and emotional intelligent toward pilot performance are rejected, while the alternative hypothesis (Ha) are accepted